2020
DOI: 10.3390/nu12030677
|View full text |Cite
|
Sign up to set email alerts
|

Unique Triterpenoid of Jujube Root Protects Cisplatin-induced Damage in Kidney Epithelial LLC-PK1 Cells via Autophagy Regulation

Abstract: Chronic exposure to cisplatin is associated with irreversible kidney impairment. In this present study, we explored the protective effects of 3-dehydroxyceanothetric acid 2-methyl ester (3DC2ME) isolated from roots of jujube (Ziziphus jujuba, Rhamnaceae) against cisplatin-induced damage in vitro. In kidney epithelial LLC-PK1 cells, western blotting and staining with specific autophagy epifluorescent dye CytoID were used to determine the molecular pathways involving autophagy. Treatment with 3DC2ME reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, we are aware that our research may exist some limitations compared to previous reports at the same scope. Firstly, the effect of muscone on other cell death pathways caused by cisplatin including autophagy [ 32 ] and nuclear factor-κB activation [ 33 ] has not been investigated yet in this study. Secondly, the experimental results are just at in vitro scope.…”
Section: Resultsmentioning
confidence: 99%
“…However, we are aware that our research may exist some limitations compared to previous reports at the same scope. Firstly, the effect of muscone on other cell death pathways caused by cisplatin including autophagy [ 32 ] and nuclear factor-κB activation [ 33 ] has not been investigated yet in this study. Secondly, the experimental results are just at in vitro scope.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, however, we have added alternative therapies gleaned from our 17 years of experience, such as zizyphus jujube, black seed oil, probiotics, pumpkin seeds, walking barefoot, and sweat therapy, all of which are beneficial in CKD. It has been reported that jujube fruits have beneficial effects for the prevention of hypertension, kidney damage, oxidative stress, and inflammation, and they also can help to decrease anxiety and depression [ 18 , 19 ]. We have also shown that jujube can aid in the control of dyslipidemia and diabetes in CKD patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trichostatin A and SAHA (broadspectrum HDAC inhibitors) and Tubastatin A (HDAC6 specific inhibitor) also protects against cisplatin nephrotoxicity in kidneys through AMPK-mTOR pathways but sensitizes cancer cells to cisplatin cytotoxicity by enhancing DNA damage [113,114,[160][161][162]. In addition, some natural products, neferine [95,163], emodin [164,165], ginsenoside Rb3 [97], oridonin [98], 3DC2ME [166], scutellarin [167,168], and rottlerin [49,112] also exert the same effect through AKT/ mTOR pathways. Of interest, trehalose regulates autophagy by rapid and transient lysosomal enlargement and membrane permeabilization (LMP) through TFEB, but does not induce mTOR [129,169].…”
Section: Activation Of Autophagymentioning
confidence: 99%